Relationship between financial mathematics, growth rate and inflation rate - Cervantes Grundy, Carlos (2015)
Financial Mathematics has a wide field of application in all disciplines and especially in the economic and financial sector that involves the central variable of capital, expressed in money, which assumes different values over time according to an interest rate agreed by the parties, debtor and creditor. Financial Mathematics is a science of daily application in the life of individuals and companies, so it is essential to understand it thoroughly, because the mistakes made with them have a direct impact on the expected results. The study of financial mathematics will allow the user, professional or student, to acquire the necessary knowledge to understand the implications of the variations in the value of money over time.